2014
DOI: 10.3390/f5020234
|View full text |Cite
|
Sign up to set email alerts
|

Tenure Issues in REDD+ Pilot Project Sites in Tanzania

Abstract: REDD+ has been proposed as a viable option for addressing climate change in the near term, and at relatively low cost. There is a broad consensus that clearly defined tenure rights are important for the implementation and success of REDD+, both to manage forests effectively and to protect local communities' livelihoods. We use primary data from 23 villages in six REDD+ pilot sites in Tanzania to identify causes of deforestation and forest degradation, and tenure rights issues, at the village level prior to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 22 publications
(18 reference statements)
0
12
0
1
Order By: Relevance
“…In 1999, Tanzania's Land Act was passed to protect community land rights and acknowledge the customary tenure system in villages. However, in the draft of the Tanzania National REDD+ Strategy , village land is taken as “general land” in conflict with the customary and statutory rights as phrased in the Act (Dokken et al ), reflecting longstanding differences between forest and land authorities. The NGOs have made efforts to secure village land certificates at the national level, but the process has been challenging and more time consuming than planned (Dokken et al ).…”
Section: Citizenship In the New Global Commonsmentioning
confidence: 99%
“…In 1999, Tanzania's Land Act was passed to protect community land rights and acknowledge the customary tenure system in villages. However, in the draft of the Tanzania National REDD+ Strategy , village land is taken as “general land” in conflict with the customary and statutory rights as phrased in the Act (Dokken et al ), reflecting longstanding differences between forest and land authorities. The NGOs have made efforts to secure village land certificates at the national level, but the process has been challenging and more time consuming than planned (Dokken et al ).…”
Section: Citizenship In the New Global Commonsmentioning
confidence: 99%
“…The aforementioned findings were variously supported by scholars such as Veit et al (2012), Sunderlin et al (2013), Okamoto et al (2012), Mbow et al (2010), Unruh (2008), McKenzie and Childless (2011) and Dokken et al (2014). Veit et al (2012), for example, observed a number of challenges relating to land tenure and forest governance in Tanzania.…”
Section: Land Tenure Conditions In Uvinza District During Redd+ Projectmentioning
confidence: 81%
“…Since people in our study areas attach considerable trust to customary tenure to secure their rights to forest resources, the formalization of customary tenure in the DRC using the kind of community-based models seen in Tanzania (see [73]) offers a promising opportunity for addressing REDD+ implementation tenure issues in the DRC. Similarly, the DRC's enactment of a community forestry law in August 2014 could further ground attempts to formalize customary rights to forestland [74].…”
Section: Institutional Pluralism: What Are the Implications For Redd+?mentioning
confidence: 99%